Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.3390/antibiotics7020034
|View full text |Cite
|
Sign up to set email alerts
|

Veterinary Students’ Knowledge and Perceptions About Antimicrobial Stewardship and Biosecurity—A National Survey

Abstract: A better understanding of veterinary students’ perceptions, attitudes, and knowledge about antimicrobial stewardship and biosecurity could facilitate more effective education of future veterinarians about these important issues. A multicenter cross-sectional study was performed by administering a questionnaire to veterinary students expected to graduate in 2017 or 2018 in all Australian veterinary schools. Four hundred and seventy-six of 1246 students (38%) completed the survey. Many students were unaware of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
45
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 53 publications
8
45
0
1
Order By: Relevance
“…Sakeena et al [30] reported that senior pharmacy students demonstrated a significantly better understanding of antibiotics and AMR when compared to junior pharmacy students in Sri Lanka. This is also similar to the findings of Hardefeldt et al [25] in a national survey of Australian veterinary students. It can be inferred that greater exposure to the prudent use of antimicrobials during clinical teaching in the final year of veterinary school may lead to greater awareness and perceptions of AMR [25].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Sakeena et al [30] reported that senior pharmacy students demonstrated a significantly better understanding of antibiotics and AMR when compared to junior pharmacy students in Sri Lanka. This is also similar to the findings of Hardefeldt et al [25] in a national survey of Australian veterinary students. It can be inferred that greater exposure to the prudent use of antimicrobials during clinical teaching in the final year of veterinary school may lead to greater awareness and perceptions of AMR [25].…”
Section: Discussionsupporting
confidence: 91%
“…This is also similar to the findings of Hardefeldt et al [25] in a national survey of Australian veterinary students. It can be inferred that greater exposure to the prudent use of antimicrobials during clinical teaching in the final year of veterinary school may lead to greater awareness and perceptions of AMR [25]. Efforts should also be intensified to expose veterinary students in Nigeria to AMR concepts in the preliminary years of their training.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In addition, students in the final 2 years of study in Australia self‐identified good knowledge of antimicrobial pharmacology (Hardefeldt et al . 2018c), although similar data are not available for other jurisdictions. Thus, it seems unlikely that inappropriate university teaching is the primary reason for underdosing of antimicrobial agents in equine and bovine practice.…”
mentioning
confidence: 99%